AN ANALYSIS ON THE MEASURES TAKEN BY FINANCE MINISTRY TO UPLIFT THE INDIAN ECONOMY DURING COVID-19 - kumar, R. Satheesh; Rawath, S. Sushma; Krishnan, S.Gokula; J, Niveditha (International Journal of Research -GRANTHAALAYAH, 2021)
This article will throw the light on impact of the global pandemic COVID-19 on the Indian economy including its detailed impact on all the sectors of the economy. The outcome of the study will also highlight the impact of the measures undertaken by the ministry of finance to tackle situations more rationally and set an example and enough basis for the policymakers to make policies for handling the situation in an effective manner.